Massachusetts - McNair, Sylvia; Kent,Deborah (New York : Children's Press, 1998)
Describes the history, geography, ecology, people, economy, cities, and sights of the Bay State, Massachusetts.
Includes bibliographical references and index.
1020L
Keywords: Massachusetts -- Juvenile literature